Effects of regional development programmes. A view of documented evaluations and an investigation of regional statistics covering the appearance of assistance programmes in Germany 1995-2015. - Diller, Christian; Nischwitz, Guido; Karic, Sarah; Arnold, Jasmin; Chojnowski, Patrick; Kohl, Martin (Taylor & Francis, 2019)
Almost three decades ago, a paradigm change in funding policies for rural regions took effect in Europe and Germany involving a move towards cooperative, actor-oriented regional development. Although meanwhile a large number of elaborated evaluations of different types on the effects of programmes for regional development was provided in particular, the results of impact evaluations do not allow distinct conclusions if the programmes have the intended impacts on the economic and demographic development of the German regions. Presented here is the first impact evaluation for Germany - if not for Europe - comprising projects and competitions from various policy fields of regional development, covering 27 programmes in five policy fields in the period from 1991 to 2016. Although die number of programmes and not the amount of funding was analysed, die results serve to strengthen doubts about the effectiveness of the regional development programmes. In any case, a simple accumulation of a large number of funded regional development activities does not have measurable effects on the demographic and economic evolution of the regions.
Keywords: Regionalentwicklung; Regionalförderung; Förderungsprogramm; Entwicklungsprogramm; Öffentliche Investition; Wirkung; Bewertung; Erfolgskontrolle; Evaluation; Methode; Monitoring; Regionalstatistik; Vergleich; EU-Förderung